ANALISIS KESULITAN MENULIS PERMULAAN TERHADAP SISWA TUNAGRAHITA RINGAN - Gloria Natalia; Elly Sukmanasa, Fitri Anjaswuri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Difficulty writing at the beginning that disabled students often experience due to cognitive and linguistic limitations. This qualitative research, employing a case study method, aims to investigate the challenges of initial writing for mildly disabled students in grade II at the school. The research subject is a mildly disabled student. Data collection techniques use observation, interviews (students, teachers, and parents), and documentation, with instruments in the form of observation guidelines, interviews (structured for teachers and parents, semi-structured for students), and documentation guidelines. Data analysis includes data reduction, presentation, and verification, as well as credibility, transferability, dependability, and confirmability tests. The results of the study showed that the subjects were able to write basic letters with help, but had difficulty writing independent sentences, distinguishing similar letters, and had low concentration. In conclusion, disabled students face complex writing difficulties, requiring an individual approach, a conducive learning environment, and teacher-parent collaboration to gradually improve their writing skills.